Self-esteem, perceived peer influences, and academic achievement among Indonesian high school students - Pawanta, Hermanus Sigit. (Animo Repository, 2002)
This study examines whether self-esteem and perceived peer influences, and their respective dimensions, predict the academic achievement of high school students. Furthermore, it identifies, which among variables self-esteem, perceived peer influences, and their respective dimensions could be considered as significant predictors of academic achievement.The subjects of the study were 299 selected male and female students 16-18 years old, all of whom were second and third year senior high school students from St. Agnes High School in Surabaya, Indonesia. Two instruments were used to gather the data: the Self-Esteem Index and Perceived Peer Influences. Meanwhile, grade point averages (GPA) were used to measure the academic achievement of the sample population. Multiple regression analysis was used in order to determine whether self-esteem, perceived peer influences and their respective dimensions could be used as predictors of academic achievement of the sample population. The findings of this study revealed that self-esteem and perceived peer influences are predictors of academic academic achievement. With regard to the dimensions of self-esteem in predicting academic achievement, the results showed that the best predictor was perception of academic competence. Moreover, regarding the dimensions of perceived peer influences, the best predictor in predicting academic achievement was identification. This study also showed that between the two dimensions, perception of academic competence was the better predictor of academic achievement. The findings of the present study support the hypothesis that academic achievement can be predicted by certain dimensions of self-esteem and perceived peer influences.